A novel method for obtaining virtual inertial response of DFIG‐based wind turbines. Issue 2 (24th February 2015) - Zhang, Xiangyu; Wang, Yi; Fu, Yuan; Xu, Lie
Abstract: This paper investigates virtual inertia control of doubly fed induction generator (DFIG)‐based wind turbines to provide dynamic frequency support in the event of sudden power change. The relationships among DFIGs' virtual inertia, rotor speed and network frequency variation are analysed, and a novel virtual inertia control strategy is proposed. The proposed control strategy shifts the maximum power point tracking (MPPT) curve to the virtual inertia control curves according to the frequency deviation so as to release the 'hidden' kinetic energy and provide dynamic frequency support to the grid. The calculation of the virtual inertia and its control curves are also presented. Compared with a PD regulator‐based inertial controller, the proposed virtual inertia control scheme not only provides fast inertial response in the event of sudden power change but also achieves a smoother recovery to the MPPT operation. A four‐machine system with 30% of wind penetration is simulated to validate the proposed control strategy. Simulation results show that DFIG‐based wind farms can provide rapid response to the frequency deviation using the proposed control strategy. Therefore, the dynamic frequency response of the power grid with high wind power penetration can be significantly improved. Copyright © 2015 John Wiley & Sons, Ltd.